Conserved and Widespread Expression of piRNA-Like Molecules and PIWI-Like Genes Reveal Dual Functions of Transposon Silencing and Gene Regulation in Pinctada fucata (Mollusca) - Huang, Songqian; Ichikawa, Yuki; Yoshitake, Kazutoshi; Kinoshita, Shigeharu; Asaduzzaman, Md; Omori, Fumito; Maeyama, Kaoru; Nagai, Kiyohito; Watabe, Shugo; Asakawa, Shuichi (Frontiers in Marine Science, 2021)
PIWI proteins and PIWI-interacting RNAs (piRNAs) suppress transposon activity in animals, thus safeguard the genome from detrimental insertion mutagenesis. Recently, evidences revealed additional targets and functions of piRNA in various animals. piRNAs are ubiquitously expressed in somatic tissues of the pearl oyster Pinctada fucata, but the role of somatic piRNAs was not well characterized. Here, we report a PIWI/piRNA pathway, including piRNA biogenesis and piRNA-mediated transposon silencing and gene regulation in P. fucata. A total of 69 piRNA clusters were identified in the genome of P. fucata based on the expression of piRNAs, which contain 26% transposons and enrich for DNA/Crypton, LINE/CR1, SINE/Deu and DNA/Academ. However, thousands of distinct piRNAs that do not match transposon elements suggest additional targets and function of piRNAs. Locked-nucleic-acid modified oligonucleotide (LNA-antagonist) was used to silencing a single piRNA (piRNA0001) expression in P. fucata. Hundreds of endogenous genes were differentially expressed after piRNA silencing in P. fucata. Target prediction showed that tens of endogenous genes were targeted by piRNA0001, including twelve up-regulated and nine down-regulated genes after piRNA0001 silencing. Zinc finger protein 622 (ZNF622), one of the predicted target genes of piRNA0001, was up-regulated in all examined somatic tissues after piRNA0001 silencing. Furthermore, bioinformatics analyses suggested that different populations of piRNAs participate in the ping-pong amplification loop in a tissue-specific manner. These findings will enhance the understanding of the role of piRNA in mollusks and would also provide an evidence to understand transposon silencing and regulatory function of PIWI/piRNA pathway on protein coding genes outside of germ line cells in P. fucata.